Evaluation of phytostabilization of mine tailings after biochar amendment. - Fellet G; Poscic F; MARCHIOL, Luca (2010)
Phytostabilization is one of the possible interventions to reduce the risks of contamination posed by mine tailings. This technique aims at reducing the mobility of the pollutants by establishing a green cover on the wastes. Recent studies, have focused the attention on biochar application to soil. Biochar is a C-rich product obtained when biomass is heated with limited oxygen supply and at relatively low temperature (<700°C). Some experiments revealed the potential benefits that biochar application induces to the soil in terms of property changes that turns into yield improvements. Biochar also seems to reducing the uptake of toxic elements by plants by reducing their bioavailability. The case study is represented by the past mining site of Cave del Predil (NE Italy) where about 20 hectares of dumping site lay undisturbed. Among the local species found on the site, Poa alpina and Anthyllis vulneraria were selected as possible candidates for phytostabilization. Two other species were selected: Festuca rubra and Buphtalmum salicifolium. The pot experiment aims at testing the four species on the following substrates: control (untreated mine tailings); 3 levels of equal rate of biochar and compost amendments applied to the mine tailings (0.5, 1 and 2%dw); the previous 4 substrates with mineral fertilization (NPK). At the end of the growing period, the plants will be harvested and the heavy metals content will be analyzed in their tissues (roots and shoots). The data from the metal uptake and accumulation and the biomass production will give important hints on the feasibility of the remediation process.